INNOVATIVE DEVELOPMENT OF GRAIN PRODUCTS SUBCOMPLEX AS THE DRIVER OF NATIONAL FOOD SECURITY PROVISION - Alexey V. RODIONOV; Mikhail N. KOZIN; Vladimir Y. PRIPOTEN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
To understand the agri-food marketing landscape, in terms of associated factors influencing the future development from the local level it is essential among others to evaluate consumers as customers of agri-food markets. It is relevant to understand their choices on what values are based on and why they became customers of agri-food markets in Sibiu city. This is only one relevant end part of the food chain aside industry and hospitality areas. Their daily philosophy of ensuring agri-food products can support in the end the cost-efficient conservation and sustainable use of genetic resources for food and agriculture required for long-term maintenance food security. The scope of this article is to evaluate the orientation of Sibiu’s consumers as customers of agri-food markets in order to understand if they are or not aware about the value of local food. These results may further support the development of public policies related to gastronomic tourism based on local products. The analysis of these results is proving that the customers of agri-food markets are aware about the value of local food and they are mostly oriented to buy them directly from producers, bypassing agri-food markets. The need to develop an appropriate infrastructure dedicated to the preservation of agri-food products appear to be one of the major barriers against trading local products, a major gap in the support of rural area development.